Pengaruh Motivasi dan Disiplin Kerja Terhadap Produktivitas Karyawan pada Industri Jamu PT. Payung Pusaka Mandiri - Elsa Febiola; Nonni Yap; Yogi Yunanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the effects of employee motivation and work discipline on employee productivity at PT. Payung Pusaka Mandiri, which operates in the jamu industry. This study employs a quantitative approach with an explanatory research design. The sample used is all 56 members of the workforce using the entire sampling method. The data is collected using a kuesioner and analyzed using a berganda line regression. The study's findings indicate that employee motivation has a positive and significant impact on their productivity in a parsial manner. Workplace discipline also has a positive and significant impact on employees' productivity in a parsial manner. Simultaneously, work discipline and motivation have a significant impact on employees' productivity. All of this highlights how important it is for businesses to consider motivational and disciplinary factors as a strategy to increase employee productivity.